One-pot reductive coupling reactions of acetyl naphthalene derivatives, tosylhydrazide, with arylboronic acids. Issue 6 (9th February 2017) - Shen, Xu; Liu, Ping; Liu, Yang; Liu, Yan; Dai, Bin
Abstract: In this study, a one-pot two-step reductive coupling between acetyl naphthalene derivatives, tosylhydrazide, and arylboronic acids, affording substituted 1(or 2)-(1-phenylethyl)naphthalenes in moderate-to-excellent yields, was reported. Notably, solvent played a crucial role in the coupling of 1-acetyl naphthalene derivatives (toluene) or 2-acetyl naphthalene derivatives (1, 4-dioxane) as starting materials. Meanwhile, the scope of this one-pot coupling reaction was extended to 1(or 2)-naphthaldehyde substrates. Particularly, the system was also suitable to synthesize 1(or 2)-(1-phenylethyl)naphthalenes on a multi-gram scale, and was applied in the synthesis of naphthylmethyl substituted carbazolyl compounds. Graphical abstract: